A survey of the dialect geography in the five towns and one barrio of Catanduanes (Caramoran, Viga, San Miguel, Virac, San Andres and Cabugao) - Dolores, Reynaldo de Luna 1927-
A survey of the dialect geography of the six Bicol speaking communities of Catanduanes, namely, Caramoran, Viga, San Miguel, Virac, San Andres, (towns) and Cabugao (barrio) was constructed in this study. It is primarily aimed at finding the dialectal variations of words from the foregoing speech communities